2011
DOI: 10.1152/ajpheart.00246.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired transient vasodilation and increased vasoconstriction to digital local cooling in primary Raynaud's phenomenon

Abstract: Raynaud's phenomenon (RP) is defined as episodic ischemia of the extremities in response to cold. Although the structure of skin capillaries is normal in primary RP, some data suggest impairment of microvascular function. We aimed at testing whether digital skin blood flow was lower in RP than in controls while cooling locally. We further evaluated the contribution of sensory nerves in the response. We recruited 21 patients with primary RP and 20 healthy volunteers matched on age and gender. After a 10-min bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The pathophysiology of primary RP is multifactorial with both vascular and neural abnormalities. The loss of CGRP- and VIP-containing nerves in the cutaneous microvasculature [ 17 , 18 ] and abnormal response of cold-sensitive nerves were described in primary adult RP patients [ 50 ]. A recent study found a strong relationship between microangiopathy and higher serum endothelin-1 and E-selectin levels in children with RP [ 40 ], although previous data had not confirmed the diagnostic value of endothelin concentration [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of primary RP is multifactorial with both vascular and neural abnormalities. The loss of CGRP- and VIP-containing nerves in the cutaneous microvasculature [ 17 , 18 ] and abnormal response of cold-sensitive nerves were described in primary adult RP patients [ 50 ]. A recent study found a strong relationship between microangiopathy and higher serum endothelin-1 and E-selectin levels in children with RP [ 40 ], although previous data had not confirmed the diagnostic value of endothelin concentration [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have used the cooling test to assess microvascular function because patients with Raynaud symptoms often experience the symptoms in response to cold or emotional stimuli. 14,16,17 However, performing a cooling test in patients with symptoms suggestive of arterial distal upper extremity disease is often painful. It would be useful to define the LDF cutoff value for vasospasm, but no gold standard exists.…”
Section: Discussionmentioning
confidence: 99%
“…Most of its vasoconstrictor effect depends on the inhibition of the NO system and on adrenergic function, 12 particularly through the translocation of α 2c ‐adrenoreceptors mediated by RhoA–Rho kinase 13 . We recently showed that local cooling–induced vasoconstriction on the fingers of patients with primary RP was increased as compared with healthy controls 6 …”
Section: Discussionmentioning
confidence: 99%
“…Although the morphology of skin capillaries is normal in primary RP, available evidence suggests that skin microvascular function is impaired 3 , 4 , 5 . Using a local cooling test, we recently showed increased digital skin vasoconstriction in participants with primary RP as compared with healthy controls 6 …”
mentioning
confidence: 90%